Memahami Maslahat Menggunakan Pendekatan Filsafat Utilitarianisme Menurut Muhammad AbÃ» Zahrah - Abdul Basith Junaidy (Islamica: Jurnal Studi Keislaman, 2014)
This paper seeks to describe the efforts of AbÃ» Zahrah in making the philosophy of utilitarianism as a means of understanding the concept of maslahah mursalah in legal reasoning. In Zahrah?s view, the principle of utilitarianism can be taken into account as a guide to understand and apply the concept of maslahah. Zahrah goes on to argue that maslahah can be applied quantitatively using the hedonic calculus as a tool of measurement. Zahrah defines maslahah as an action that is valued as having the greatest benefit for the majority of people in the long term. In his opinion, there are seven factors that determine the level of satisfaction and pain resulted from an action, namely intensity, duration, certainty, propinquity, fecundity, purity, and extent. The calculation will produce positive balance if the credit (satisfaction) is much greater than the debt (pain). This calculus, according to Zahrah, can be applied to measure the benefit and loss in the discourses of maslahah mursalah.